Testing of Chemical and Physical Properties Test of Egg Cane Crackers (Saccharum Edule) with Variations of Wheat Flour and Tapioca Flour - Selvianti Sari, Yuni; Vieni Sari, Sethyo; Beni, Yulius (Green Publisher Indonesia, 2024)
Egg sugarcane (Saccharum edule) is a vegetable plant that is widely found in Indonesia, especially in Sanggau Regency, West Kalimantan. This plant resembles sugar cane with bulging shoots and yellowish-white strands like fish eggs. Its use has been limited as a processed vegetable ingredient. To increase economic value and extend its shelf life, processed innovations in the form of egg sugarcane crackers are carried out. This study aims to determine the chemical properties, fertility, and preferences of the panelists for egg sugarcane crackers with variations of wheat flour and tapioca flour. The observed parameters included moisture content, ash, protein, fat, crude fiber, carbohydrates, fertility, and hedonic organoleptic test. The results of the study showed that the chemical properties of egg cane crackers varied. The highest moisture content values were in A2 treatment (9.26% wb; 8.79% db), the highest ash content in A2 (3.35% wb; 3.64% db), the highest fat content in A2 (2.10%), the highest protein content in A1 (8.46%), the highest crude fiber in A3 (6.70%), and the highest carbohydrate in A3 (73.72%). The best flowering power was found in the A1 treatment (76.84%). The panelists' preference for color was highest at A3 (5.77), aroma at A2 (5.40), taste at A3 (5.87), and texture at A3 (5.67). These results show that the variation of wheat flour and tapioca affects the chemical quality, floweriness, and preference of panelists for egg cane crackers, making it an innovative product with potential economic added value.